Experiences of the disabled women attending the state-provided reproductive health care services regarding the quality of care rendered by health care professionals in the Eastern Cape - Mgwili, Victoria Nokwanele (Department of Health and Rehabilitation Sciences, 2015)
The purpose of this study was to explore and describe the experiences of disabled women, attending the state-provided reproduction health services, regarding the quality of care rendered by health professionals in the Eastern Cape. The study was conducted on disabled women at Flagstaff and Lusikisiki self-help group project sites.